Advance Care Planning in Home Health: A Review of the Literature. Issue 6 (December 2019) - Bigger, Sharon; Haddad, Lisa
Abstract : The purpose of this article is to synthesize the evidence on advance care planning (ACP), determine what is applicable to the home health (HH) setting, and find where gaps in knowledge may exist. An integrative review methodology was chosen. Although there is ample literature on the topic of ACP, most research has been conducted in the acute care, outpatient, and general community settings. There is limited literature regarding ACP with patients living with chronic cardiovascular and pulmonary illnesses, who comprise the majority of the HH population. Some literature has been published regarding the interprofessional team's role in ACP in the HH setting. A gap in knowledge exists regarding ACP in HH, and recommendations for future research are provided. Abstract : Supplemental digital content is available in the text.